Fault Diagnosis Approach of Gear based on Two Features and Least Squares Support Vector Machine - Qin Bo; Yang Yunzhong; Chen Min; Guo Wei; Liu Yongliang; Wang Jianguo (Jixie chuandong)
Aiming at the Gear vibration signals have the nonlinear and non-stationary characteristics,to avoid the disadvantages of traditional time and frequency domain method in the characterization of the state of equipment and failure identification model "less learning"problem caused by small sample size,the gearbox fault diagnosis method based on kurtosis and intrinsic mode function（ IMF） energy feature and least squares support vector machine（ LS-SVM） is proposed. Firstly,by using ensemble empirical mode decomposition（ EEMD）,the collected gear vibration signal is decomposed,on this basis,the IMF components which contain major fault information are extracted and its energy feature and kurtosis are calculated,and the time-frequency domain two kinds of the feature vector are constructed. Secondly,taking the fusion feature vectors of three conditions of normal,the root crack and broken as input,the gearbox fault type identification is conducted based on the LS-SVM. The experiment results show that the gear working state can be accurately identified by this method. It has higher efficiency of fault identification compared with the BP neural network and SVM model and a new way for the gear fault diagnosis is provided.